Drugs in the Caribbean : an economic balance sheet. - GRIFFITH, Ivelaw L. (1995)
Discusses the costs and benefits of the drug phenomenon within the context of the region's economic circumstances. Identifies three areas of actual and potential economic benefits as : employment, income regeneration, and revenue enhancement. Negative aspects of the drug trade include its impact on certain industries, fines imposed by foreign countries, and resource utilization. Concludes that, in addition to operational countermeasures to deal with production, trafficking and other operations, and with crime, corruption and other consequences of the phenomenon, also needed are structural and functional adaptations in the economic sphere in order to remove some of the incentives for involvement in drugs.